MCENT BROWSER APPLICATION IN ISLAMIC LAW - masitoh nurul anisa (Jurnal Ilmiah Pesantren, 2022)
The purpose of this research is to discover the mechanism of mCent Browser application in Islamic law. This research is conducted using library-researched study. The research information is compiled from the library information by reviewing and comprehending the things that are considered important related to the discussion. Furthermore, this researched is analyzed by the deduction method and theory of Ushul Fiqh. The result from this study is that the mCent Browser application is included as a buy and sell application which is not clear. There is a chance of speculation, as well as elements of fraud, that can evoke animosity between two parties that transact, or one party deceiving the other party, and this is forbidden by the Prophet Muhammad SAW.